2017
DOI: 10.1097/igc.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

Possible Risk Factors of Pulmonary Metastases in Patients With International Federation of Gynecology and Obstetrics Stage I Endometrioid-Type Endometrial Cancer

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Some studies showed that squamous differentiation is a risk factor for endometrial cancer recurrence. 13, 21 A retrospective study of 223 patients with early-stage endometrial cancer, carried out by Misirlioglu et al , similar with our study, regarding methodological structure, showed squamous differentiation as a risk factor for recurrence in early-stage endometrial cancer. 13 The authors reported 10.31% of recurrence (23 cases), very similar to that found in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies showed that squamous differentiation is a risk factor for endometrial cancer recurrence. 13, 21 A retrospective study of 223 patients with early-stage endometrial cancer, carried out by Misirlioglu et al , similar with our study, regarding methodological structure, showed squamous differentiation as a risk factor for recurrence in early-stage endometrial cancer. 13 The authors reported 10.31% of recurrence (23 cases), very similar to that found in our study.…”
Section: Discussionsupporting
confidence: 87%
“…There are several patterns of metastatic spread from EC, including intra-abdominal spread and lymph node involvement; however, distant organ metastasis involving the lungs, liver, brain, or bone is considered a unique situation. [2][3][4][5] Although distant organ metastasis is a rare event in EC, it has important implications and is associated with substantially shortened survival. 6,7 Moreover, the specific site of distant metastasis can influence survival for women with EC, and it is important to understand the patterns of metastasis in newly diagnosed cases in order to more accurately predict prognosis and select an appropriate management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with stage IVB endometrial carcinoma and deep myometrial invasion are at increased risk for lung metastasis 2. The risk factor associated with lung metastasis in our patient was the deep myometrial invasion 3. Surgical resection followed by systemic chemotherapy is the standard of care.…”
Section: Descriptionmentioning
confidence: 72%